FROM TRADITIONAL ACCOUNTING TO KNOWLEDGE BASED ACCOUNTING ORGANIZATIONS - NICOLETA RADNEANTU; EMILIA GABROVEANU; ROXANA STAN (Annals of the University of Petrosani: Economics)
Nowadays, we may observe that the rules of traditional economy have changed. The new economy – the knowledge based economy determine also major change in organizations resources, structure, strategic objectives, departments, accounting, goods. In our research we want to underline how the accounting rules, regulations and paradigms have changed to cope with political, economic and social challenges, as well as to the emergence of knowledge based organization. We also try to find out where Romanian accounting is on the hard road of evolution from traditional to knowledge based.